Carbon material dispersion liquid and application thereof

By using polymer dispersants with specific structures and alkali neutralized carboxyl groups, combined with water-soluble organic solvents, the problems of insufficient dispersion and poor stability of carbon material dispersion at high concentrations are solved, and excellent dispersion and long-term stability are achieved, and it is suitable for the manufacture of a variety of materials.

CN119585359APending Publication Date: 2025-03-07DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055691.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-04-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing carbon material dispersions are insufficient in dispersion at high concentrations and have poor long-term stability, which can easily lead to the settlement of carbon material or gelation of dispersions.

Method used

A polymer dispersant with 50 to 80 mass % of the (meth)acrylonitrile structural unit and 20 to 50 mass % of the (meth)acrylic acid structural unit is used to form an excellent carbon material dispersion liquid with a alkali-neutralized carboxyl group and a water-soluble organic solvent.

Benefits of technology

It achieves excellent dispersion and long-term stability of carbon materials at high concentrations, and is suitable for the manufacture of coatings, inks, conductive materials and antistatic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005253895770000131
    Figure BDA0005253895770000131
  • Figure BDA0005253895770000151
    Figure BDA0005253895770000151
  • Figure BDA0005253895770000181
    Figure BDA0005253895770000181
Patent Text Reader

Abstract

Provided is a carbon material dispersion which exhibits excellent dispersibility of a carbon material even when the carbon material is contained at a high concentration, and which stably maintains dispersibility over a long period of time. A carbon material dispersion liquid containing at least one carbon material selected from the group consisting of carbon black, carbon fibers, carbon nanotubes, graphite and graphene, water, and a polymer dispersant which is a polymer having a carboxyl group at least partially neutralized by an alkali, the polymer has 50-80% by mass of a structural unit (1) derived from (meth) acrylonitrile and 20-50% by mass of a structural unit (2) derived from (meth) acrylic acid (where the total of the structural unit (1) and the structural unit (2) is 100% by mass), and has a number average molecular weight of 10,000-50,000.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon material dispersion and applications thereof. Background Art

[0002] Carbon materials (nanocarbon materials) such as carbon black, carbon fiber, carbon nanotubes, graphite, and graphene have a six-membered ring graphite structure formed by covalent bonds of carbon atoms, and are materials that exert various properties such as electrical conductivity and thermal conductivity. Methods for making these properties work in various fields are being studied. For example, attention is paid to the electrical properties, thermal properties, and properties of carbon materials as fillers, and research is being conducted on their application in antistatic agents, conductive materials, plastic reinforcement materials, semiconductors, fuel cell electrodes, and cathode lines of displays.

[0003] For these uses, a carbon material dispersion liquid is required that has good dispersibility of the carbon material and maintains the dispersibility for a long time. However, nano-sized carbon materials have high surface energy and strong van der Waals forces act, so they are easy to aggregate. Therefore, even when dispersed in a liquid medium, they often aggregate immediately.

[0004] In order to stably disperse the carbon material in a liquid medium, a dispersant is generally used. For example, solvent-based dispersions of carbon nanotubes using cationic surfactants such as alkanolamine salts and polymer dispersants such as styrene-acrylic resins have been proposed (Patent Documents 1 and 2).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2010-174084

[0008] Patent Document 2: Japanese Patent Application No. 2013-537570 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] If a surfactant is used as a dispersant, carbon materials such as carbon nanotubes can be dispersed in a liquid medium. However, it can be said that the dispersibility of the carbon material in the obtained dispersion is not necessarily excellent, and there is also a problem of easy re-aggregation. In addition, if a conventional polymer dispersant is used, the obtained dispersion is prone to thixotropic properties. Therefore, there is a situation where the carbon material settles or the dispersion gels over time.

[0011] The present invention is made in view of the problems of the prior art, and its subject is to provide a carbon material dispersion liquid which has excellent dispersibility of the carbon material even when the carbon material is contained at a high concentration and maintains the dispersibility stably for a long time. In addition, the subject of the present invention is to provide an application of the carbon material dispersion liquid.

[0012] Solutions for solving problems

[0013] That is, according to the present invention, the following carbon material dispersion is provided.

[0014] [1] A carbon material dispersion comprising: at least one carbon material selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite and graphene, water, and a polymer dispersant, wherein the polymer dispersant is a polymer having carboxyl groups at least partly neutralized by an alkali, and having 50 to 80% by mass of a structural unit (1) derived from (meth)acrylonitrile and 20 to 50% by mass of a structural unit (2) derived from (meth)acrylic acid (wherein the total of the structural unit (1) and the structural unit (2) is 100% by mass), and the number average molecular weight of the polymer is 10,000 to 50,000.

[0015] [2] The carbon material dispersion according to [1], wherein the polymer is an AB block copolymer comprising a polymer segment A and a polymer segment B, wherein the polymer segment A comprises 60 to 95% by mass of a structural unit (1-A) derived from acrylonitrile and 5 to 40% by mass of a structural unit (2-A) derived from methacrylic acid (wherein the total of the structural unit (1-A) and the structural unit (2-A) is 100% by mass), and the polymer segment B comprises 10 to 70% by mass of a structural unit (1-B) derived from acrylonitrile and 30 to 90% by mass of a structural unit (2-B) derived from methacrylic acid (wherein the total of the structural unit (1-B) and the structural unit (2-B) is 100% by mass), and the number average molecular weight of the polymer segment A is 8,000 to 40,000, and the molecular weight distribution is 1.8 or less.

[0016] [3] The carbon material dispersion according to [1] or [2], wherein the base is at least one selected from the group consisting of lithium hydroxide, sodium hydroxide and potassium hydroxide, and the amount of the base is an amount equivalent to 50 to 120 mol % of the carboxyl groups.

[0017] [4] A carbon material dispersion according to any one of [1] to [3] above, which further contains at least one water-soluble organic solvent selected from the group consisting of dimethylformamide, dimethylacetamide, diethylacetamide, N-methylpyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, tetramethylurea, 1,3-dimethylimidazolidinone and acetonitrile.

[0018] [5] The carbon material dispersion according to any one of [1] to [4] above, wherein the content of the polymer dispersant is 10 to 350 parts by mass relative to 100 parts by mass of the carbon material, and the content of the carbon material is 15% by mass or less.

[0019] [6] The carbon material dispersion according to any one of [1] to [5] above, further comprising a binder resin.

[0020] Furthermore, according to the present invention, there are provided uses of the carbon material dispersion liquid shown below.

[0021] [7] Use of the carbon material dispersion described in any of [1] to [6] above for manufacturing any product selected from the group consisting of paint, ink, coating agent, resin molding material, conductive material, thermal conductive material and antistatic material.

[0022] [8] Use of the carbon material dispersion according to any one of [1] to [6] above for producing a product including a battery material and a mechanical part having a coating formed of the carbon material dispersion.

[0023] Effects of the Invention

[0024] According to the present invention, it is possible to provide a carbon material dispersion liquid which has excellent dispersibility of the carbon material even when the carbon material is contained at a high concentration and which stably maintains the dispersibility for a long period of time. In addition, according to the present invention, it is possible to provide an application of the carbon material dispersion liquid.

[0025] The carbon material dispersion of the present invention is excellent in dispersibility, storage stability, viscosity characteristics and processability, and can easily form a carbon coating by coating, etc. In addition, by appropriately selecting the carbon material, it is also expected to form a highly transparent coating. Furthermore, even if the content of the polymer dispersant is small, the carbon material is dispersed in a good state, so that a coating with a large content of the carbon material can be formed, and it is expected to exert the characteristics of the carbon material itself such as electrical conductivity and thermal conductivity. DETAILED DESCRIPTION

[0026] <Carbon material dispersion>

[0027] The embodiments of the present invention are described below, but the present invention is not limited to the following embodiments. One embodiment of the carbon material dispersion of the present invention is an aqueous dispersion of a carbon material containing a carbon material, water, and a polymer dispersant. The details of the carbon material dispersion of the present invention are described below.

[0028] (Carbon material)

[0029] The carbon material is at least one selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite and graphene. Examples of carbon black include acetylene black, furnace black, thermal black, Ketjen black and the like.

[0030] As the carbon nanotubes, multi-layered multi-walled carbon nanotubes and single-layered single-walled carbon nanotubes can be used. The average length of the multi-walled carbon nanotubes is preferably 40 to 3000 μm. The average length of the single-walled carbon nanotubes is preferably 5 to 600 μm.

[0031] As carbon fibers, PAN-based carbon fibers made of polyacrylonitrile as raw materials, pitch-based carbon fibers made of pitch as raw materials, and their regenerated products can be cited. Among them, so-called carbon nanofibers having a nanometer-sized fiber diameter and a shape in which a six-membered ring graphite structure is rolled into a cylindrical shape or carbon nanotubes having a single nanometer-sized diameter are preferred. Carbon nanofibers and carbon nanotubes can be any of multilayers and single layers.

[0032] Graphite is a layered substance consisting of hexagonal plate-like crystals composed of carbon. Among them, graphene, which is a single layer obtained by exfoliating graphite and having a thickness of one atom, and graphene consisting of multiple layers can be used.

[0033] The carbon material may be doped with metals or metal salts such as platinum and palladium. In addition, the carbon material may be surface-modified by oxidation treatment, plasma treatment, radiation treatment, corona treatment, coupling treatment, and the like.

[0034] (Polymer dispersant)

[0035] A polymer dispersant (hereinafter also referred to as "dispersant") is a component for dispersing a carbon material in a dispersion medium (liquid medium) containing water, and is a polymer having carboxyl groups at least partly neutralized by a base. More specifically, the polymer dispersant is a polymer having a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid, and is preferably a polymer consisting essentially of a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid.

[0036] Structural unit (1) has a cyano group (-CN) derived from (meth) acrylonitrile. Therefore, the triple bond of the cyano group acts on the surface of the carbon material, and the polymer as a dispersant is adsorbed on the carbon material in an electronic manner. In addition, structural unit (2) has a carboxyl group derived from (meth) acrylic acid. Therefore, by neutralizing at least a portion of the carboxyl group with a base to ionize it, the polymer as a dispersant can be dissolved in a liquid medium containing water. By using a polymer containing these structural units (1) and structural units (2) as a dispersant, the carbon material can be microdispersed in a liquid medium containing water for a long time.

[0037] The proportion of the structural unit (1) derived from (meth) acrylonitrile in the polymer is 50 to 80% by mass, preferably 55 to 75% by mass. In addition, the proportion of the structural unit (2) derived from (meth) acrylic acid in the polymer is 20 to 50% by mass, preferably 25 to 45% by mass. It should be noted that the total of the structural unit (1) and the structural unit (2) is set to 100% by mass. If the proportion of the structural unit (2) in the polymer is less than 20% by mass, the water solubility of the polymer is insufficient. On the other hand, if the proportion of the structural unit (2) in the polymer exceeds 50% by mass, the water solubility of the polymer becomes too high. Therefore, while the viscosity of the carbon material dispersion is excessively increased, the amount of hydrophilic carboxyl groups is large, and therefore, the water resistance of the formed coating is sometimes reduced.

[0038] The polymer dispersant (polymer) may further have other structural units in addition to the structural unit (1) and the structural unit (2). Examples of monomers constituting other structural units include conventionally known styrene monomers, (meth)acrylate monomers, and the like. Among them, it is preferred to use monomers that do not contain easily hydrolyzable structures such as ester bonds and amide bonds. Examples of such monomers include styrene, vinylnaphthalene, vinyltoluene, vinylbiphenyl, vinyl alcohol, and the like.

[0039] The number average molecular weight of the polymer used as the polymer dispersant is 10,000 to 50,000, preferably 12,000 to 45,000. If the number average molecular weight of the polymer is less than 10,000, it becomes easy to desorb even if adsorbed on the carbon material, so it sometimes becomes difficult to improve the dispersion stability. On the other hand, if the number average molecular weight of the polymer exceeds 50,000, the viscosity sometimes becomes too high. The number average molecular weight in this specification is a value converted to polystyrene or polymethyl methacrylate measured by gel permeation chromatography using N,N-dimethylformamide as the developing solvent.

[0040] The polymer used as the high molecular weight dispersant is preferably an AB block copolymer comprising a polymer segment A and a polymer segment B, wherein the polymer segment A has a structural unit (1-A) derived from acrylonitrile and a structural unit (2-A) derived from methacrylic acid, and the polymer segment B has a structural unit (1-B) derived from acrylonitrile and a structural unit (2-B) derived from methacrylic acid. It should be noted that the polymer segment A is preferably a polymer segment substantially composed of only the structural unit (1-A) derived from acrylonitrile and the structural unit (2-A) derived from methacrylic acid. In addition, the polymer segment B is preferably a polymer segment substantially composed of only the structural unit (1-B) derived from acrylonitrile and the structural unit (2-B) derived from methacrylic acid.

[0041] The ratio of the structural unit (1-A) derived from acrylonitrile in the polymer segment A (hereinafter also referred to as "A chain") is preferably 60 to 95% by mass, more preferably 65 to 90% by mass. In addition, the ratio of the structural unit (2-A) derived from methacrylic acid in the A chain is preferably 5 to 40% by mass, more preferably 10 to 35% by mass. The total of the structural unit (1-A) and the structural unit (2-A) is 100% by mass.

[0042] The A chain is a polymer chain segment having a lower carboxyl content than the polymer chain segment B (hereinafter also referred to as "B chain") and relatively low water solubility. Therefore, the A chain adsorbed on the carbon material is less likely to desorb than the B chain, and thus has the function of further improving the dispersibility of the carbon material. If the proportion of the structural unit (2-A) in the A chain is less than 5% by mass, the water solubility of the A chain is sometimes insufficient. On the other hand, if the proportion of the structural unit (2-A) in the A chain exceeds 40% by mass, the water solubility of the A chain sometimes becomes too high, and sometimes it becomes easy to desorb from the carbon material.

[0043] The number average molecular weight of the polymer segment A (A chain) is preferably 8000 to 40000, and more preferably 10000 to 35000. If the number average molecular weight of the A chain is less than 8000, the adsorption to the carbon material may be insufficient. On the other hand, if the number average molecular weight of the A chain exceeds 40000, even if the structural unit (2-A) having a carboxyl group is provided, the water solubility may become insufficient.

[0044] The molecular weight distribution (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) of the polymer segment A (A chain) is preferably 1.8 or less, and more preferably 1.6 or less. Since the molecular weight is relatively uniform, it can be adsorbed more uniformly on the carbon material and the dispersibility can be further improved. If the molecular weight distribution (PDI value) of the A chain exceeds 1.8, a large amount of polymer segments outside the above-mentioned number average molecular weight range are included, and thus the effect of improving the dispersibility may be reduced.

[0045] The ratio of the structural unit (1-B) derived from acrylonitrile in the polymer segment B (B chain) is preferably 10 to 70% by mass, more preferably 15 to 65% by mass. In addition, the ratio of the structural unit (2-B) derived from methacrylic acid in the B chain is preferably 30 to 90% by mass, more preferably 35 to 85% by mass. It should be noted that the total of the structural unit (1-B) and the structural unit (2-B) is 100% by mass.

[0046] The B chain is a polymer segment containing more carboxyl groups and having relatively high water solubility compared to the A chain. If the ratio of the structural unit (2-B) in the B chain is less than 30% by mass, the water solubility of the AB block copolymer as a whole is sometimes insufficient. On the other hand, if the ratio of the structural unit (2-B) in the B chain exceeds 90% by mass, the water affinity sometimes becomes too high. Therefore, when the viscosity of the carbon material dispersion liquid becomes excessively high, the water resistance of the formed coating film is sometimes reduced.

[0047] The AB block copolymer can be produced, for example, by a living radical polymerization method. It should be noted that the AB block copolymer is composed of acrylonitrile and methacrylic acid, so its structure is easy to control and the molecular weight is also easy to adjust.

[0048] As the base for neutralizing at least a part of the carboxyl groups in the high molecular weight dispersant (polymer), for example, ammonia; organic amines such as triethylamine and dimethylaminoethanol; alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide; and the like, conventionally known bases can be used. Among them, from the viewpoints of improving water solubility and improving the conductivity of the coating film due to ionic action, the base is preferably at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide.

[0049] All carboxyl groups in the polymer can be neutralized with a base, but as long as the polymer is soluble in water, it is also preferred to neutralize only a portion of the carboxyl groups with a base. The carboxyl groups (-COOH) that are not neutralized with a base can hydrogen bond with the carbon material. Therefore, if a polymer in which only a portion of the carboxyl groups are neutralized with a base is used as a dispersant, the dispersibility stability of the carbon material dispersion can be further improved. The amount of the base to neutralize the carboxyl groups is preferably an amount equivalent to 50 to 120 mol% of the carboxyl groups, and more preferably an amount equivalent to 70 to 110 mol% of the carboxyl groups.

[0050] The polymer used as a polymer dispersant can be manufactured according to a conventionally known method. Among them, it can be manufactured by a solution polymerization method using an organic solvent; a radical polymerization method using an azo radical initiator or a peroxide radical initiator; and the like. As an organic solvent, a conventionally known organic solvent can be used. However, polymers are sometimes not easily dissolved in common organic solvents, and therefore, it is preferred to use a polar organic solvent that can be dissolved in water. As such a polar organic solvent, there can be cited amide solvents, sulfoxide solvents, urea solvents, and nitrile solvents. Among them, amide solvents, urea solvents, and nitrile solvents are preferably used. After polymerization in these organic solvents, an alkaline aqueous solution is added to neutralize the carboxyl group and aqueous solution is obtained, thereby obtaining a carbon material dispersion containing an organic solvent.

[0051] Examples of amide solvents include dimethylformamide, dimethylacetamide, diethylacetamide, N-methylpyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, etc. Examples of urea solvents include tetramethylurea, 1,3-dimethylimidazolidinone, etc. Examples of nitrile solvents include acetonitrile, etc.

[0052] It is difficult to produce the AB block copolymer used as a polymer dispersant by conventional free radical polymerization. Therefore, the AB block copolymer is preferably produced by a polymerization method with activity such as living anion polymerization, living cationic polymerization and living free radical polymerization. Among them, living free radical polymerization is particularly preferred from the viewpoints of conditions, materials and devices.

[0053] As living radical polymerization, atom transfer radical polymerization (ATRP), reversible addition fragmentation chain transfer polymerization (RAFT), nitroxide free radical regulation polymerization (NMP), organic tellurium regulation polymerization (TERP), reversible chain transfer catalytic polymerization (RTCP), reversible complex mediated polymerization (RCMP) etc. can be cited. Among them, preferably use organic compound as catalyst and use organic iodide as polymerization initiation compound RTCP, RCMP method. These methods use safer commercially available compounds, do not use heavy metals, special compounds, cost and purification are advantageous. And then, by making the growth end become trivalent iodine, thus can easily form accurate block structure with general equipment.

[0054] When producing the AB block copolymer, any of the polymer segments A and B may be polymerized first. However, if the polymer segment B is polymerized first, methacrylic acid may remain in the polymerization system. In this case, an excessive amount of structural units derived from methacrylic acid may be introduced into the polymer segment A polymerized later. Therefore, it is preferred to polymerize the polymer segment A first and then polymerize the polymer segment B.

[0055] (Liquid medium)

[0056] The carbon material dispersion of the present embodiment contains water as a dispersion medium (liquid medium) for dispersing the carbon material. That is, the carbon material dispersion of the present embodiment is an aqueous dispersion. The dispersion medium may contain a liquid medium other than water as required. As a liquid medium other than water, a water-soluble organic solvent may be used.

[0057] Examples of the water-soluble organic solvent include alcohols such as methanol, ethanol, and isopropanol; polyols such as ethylene glycol, propylene glycol, and glycerol; ethers such as tetrahydrofuran; glycol ethers such as diethylene glycol, triethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol monomethyl ether, and tripropylene glycol monomethyl ether; glycol ether esters such as diethylene glycol monomethyl ether acetate; amides such as pyrrolidone, N-methylpyrrolidone, dimethylformamide, dimethylacetamide, 3-methoxy-N,N-dimethylpropionamide, and 3-butoxy-N,N-dimethylpropionamide; urea-based solvents such as tetramethylurea and dimethyl-1,3-imidazolidinone; sulfur-containing solvents such as dimethyl sulfoxide and cyclopentane; ionic liquids such as 1-ethyl-3-methylimidazolium chloride; and the like.

[0058] Among them, it is preferred to directly contain a solvent used when polymerizing the polymer dispersant as a liquid medium. That is, the carbon material dispersion of the present embodiment preferably also contains at least one water-soluble organic solvent selected from the group consisting of dimethylformamide, dimethylacetamide, diethylacetamide, N-methylpyrrolidone, 3-methoxy-N, N-dimethylpropionamide, 3-butoxy-N, N-dimethylpropionamide, tetramethylurea, 1,3-dimethylimidazolidinone and acetonitrile. By using these water-soluble organic solvents, the wettability of the carbon material to the dispersion medium can be improved. Furthermore, the leveling property of the formed coating can be improved, and the formed coating can be given functions such as anti-drying.

[0059] The content of the water-soluble organic solvent in the carbon material dispersion is preferably 20% by mass or less, more preferably 10% by mass or less.

[0060] (Carbon material dispersion)

[0061] The content of the polymer dispersant in the carbon material dispersion is preferably 10 to 350 parts by mass, more preferably 20 to 300 parts by mass, and particularly preferably 30 to 250 parts by mass, relative to 100 parts by mass of the carbon material. In addition, the content of the carbon material in the carbon material dispersion is preferably 15% by mass or less. By setting the content of the polymer dispersant relative to the carbon material to the above range, a carbon material dispersion in which the carbon material is more stably dispersed can be formed. When the polymer dispersant is too little relative to the carbon material, the dispersibility sometimes becomes slightly insufficient. On the other hand, when the polymer dispersant becomes too much relative to the carbon material, the carbon material dispersion becomes easy to thicken, and the ratio of the carbon material in the solid component sometimes becomes relatively low.

[0062] The carbon material dispersion liquid preferably further contains a binder resin. By containing a binder resin (hereinafter also referred to as a "binder"), a conductive coating film having excellent properties such as elongation and bending and further improved adhesion to a substrate can be formed. As the binder resin, if the affinity with the polymer dispersant is considered, a cellulose derivative such as carboxymethyl cellulose (including Na salt); a styrene-butadiene copolymer; an acrylic resin such as a styrene-acrylic resin is preferably used.

[0063] When a carbon material dispersion is used as a material or coating for forming a coating film, the content of the binder resin in the carbon material dispersion is preferably set to 0.3 to 200 parts by mass, and more preferably set to 3 to 100 parts by mass, relative to 1 part by mass of the carbon material. If the amount of the binder resin is too small, the coating on the substrate becomes slightly difficult, and the homogeneity of the coating film is sometimes insufficient. On the other hand, if the amount of the binder resin is too much, the amount of the carbon material becomes relatively small, and therefore, the conductivity of the formed coating film sometimes becomes slightly insufficient.

[0064] When a carbon material dispersion is used as a material for forming a coating of an electrode constituting a battery material, the content of the binder resin in the carbon material dispersion is preferably set to 0.5 to 500 parts by mass, and more preferably set to 5 to 300 parts by mass relative to 1 part by mass of the carbon material. If the amount of the binder resin is too small, coating the substrate becomes slightly difficult, and sometimes it becomes difficult to obtain a homogeneous electrode. On the other hand, if the amount of the binder resin is too much, the amount of carbon material that functions as an active material becomes relatively small, and therefore, the capacity of the resulting battery sometimes becomes insufficient.

[0065] The carbon material dispersion may further contain additives, resins, etc. As additives, water-soluble dyes, pigments, ultraviolet absorbers, light stabilizers, antioxidants, leveling agents, defoamers, preservatives, mildew inhibitors, photopolymerization initiators, and other pigment dispersants may be cited. As resins, polyolefin resins, polyhalogenated olefin resins, polyester resins, polyamide resins, polyimide resins, polyether resins, polyvinyl resins, polystyrene resins, polyvinyl alcohol resins, polymethacrylate resins, polyurethane resins, polyepoxy resins, polyphenolic resins, polyurea resins, polyethersulfone resins, etc. may be cited.

[0066] (Method for producing carbon material dispersion)

[0067] The carbon material dispersion of the present embodiment can be prepared by using the aforementioned polymer as a polymer dispersant and dispersing the carbon material in a dispersion medium (liquid medium) having water as the main component according to a conventionally known method. For example, a dispersion method such as stirring with a disperser, kneading with a three-roll mill, ultrasonic dispersion, bead mill dispersion, emulsification device, dispersion using a high-pressure homogenizer, etc. can be used. Among them, bead mill dispersion, ultrasonic dispersion, and dispersion using a high-pressure homogenizer are preferred from the perspective of high dispersion effect.

[0068] (Method for Confirming Dispersion State of Carbon Material)

[0069] The dispersibility of the carbon material in the carbon material dispersion can be confirmed by the method shown below, which uses a spectrophotometer to measure the absorbance. First, prepare a plurality of dispersions of extremely low concentrations in which the concentration of the carbon material is known, and measure the absorbance of these dispersions at a specific wavelength, and prepare in advance a standard curve that plots the absorbance relative to the concentration of the carbon material. Then, the carbon material dispersion is centrifuged to separate the carbon material that is not completely dispersed by sedimentation to obtain a supernatant. The obtained supernatant is diluted in a manner that allows the absorbance to be measured, the absorbance is measured, and the concentration of the carbon material is calculated from the standard curve. By comparing the calculated concentration of the carbon material with the amount of carbon material input, the dispersibility of the carbon material can be evaluated.

[0070] In addition, the carbon material dispersion after centrifugal separation is allowed to stand for a long time, and the presence or absence of aggregates is confirmed, thereby confirming the dispersibility of the carbon material. Furthermore, the dispersibility of the carbon material can also be confirmed by observing the state of the carbon material dispersion dripped onto a glass plate or the like using an electron microscope or measuring the physical properties such as the conductivity of a film formed by applying and drying the carbon material dispersion.

[0071] <Application of Carbon Material Dispersion Liquid>

[0072] The carbon material dispersion of the present embodiment is an aqueous dispersion, and therefore, is an environmentally friendly material, and is useful as a material for manufacturing coatings, inks, coating agents, resin molding materials, etc. In addition, it can be expected to be used as a conductive material, a thermal conductive material, and also expected to be used as an antistatic material. Furthermore, it is useful as a material for forming a battery material such as an electrode material for a battery such as a lithium ion battery, a fuel cell, a capacitor material coating, and a coating constituting various mechanical parts.

[0073] Aqueous paint or ink can be prepared by adding various components such as solvents, resins, and additives to the carbon material dispersion. Alternatively, the carbon material dispersion may be added to commercially available paint or ink.

[0074] The resin molded article can be manufactured by, for example, adding a carbon material dispersion to a molten plastic material and then removing water. Alternatively, the resin molded article in which the carbon material is dispersed can be manufactured by adding a carbon material dispersion to a fine powder plastic material and then removing water or precipitating the carbon material. Specific embodiments

[0076] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. It should be noted that "parts" and "%" in Examples and Comparative Examples are based on mass unless otherwise specified.

[0077] <Synthesis of polymer dispersants (polymers)>

[0078] (Synthesis example 1)

[0079] Place 233.3 parts of N-methylpyrrolidone (NMP) in a reaction container and stir, and heat to 70°C. In addition, place 70 parts of acrylonitrile (AN), 30 parts of acrylic acid (AA), and 5.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (trade name "V-65", manufactured by FUJIFILM Wako Chemicals Corporation) (V-65) in a beaker, and completely dissolve V-65 to prepare a monomer solution. Add the prepared monomer solution to the dropping funnel, and when the temperature in the reaction container reaches 70°C, add 1 / 3 of the total amount, and add the remaining liquid dropwise over 1.5 hours. After the addition is completed, add 1.0 part of V-65 after 2.5 hours. After maintaining at 70°C for 1 hour, raise the temperature to 80°C and maintain for 2 hours to form a polymer. After cooling, use a moisture meter to measure the solid content to confirm that all monomers are basically consumed. The number average molecular weight (Mn) of the polymer calculated as polymethyl methacrylate, measured by gel permeation chromatography (GPC) using a lithium bromide N,N-dimethylformamide solution (lithium bromide concentration: 10 mmol / L) as a developing solvent, was 14,400, and the molecular weight distribution (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) was 2.85.

[0080] 18.3 parts of sodium hydroxide (NaOH) (110 mol% relative to AA) and 83.2 parts of ion exchange water were placed in a beaker to completely dissolve NaOH to prepare a NaOH aqueous solution. After the temperature in the reaction container reached 60°C or less, the NaOH aqueous solution was added to neutralize the carboxyl group to obtain a polymer dispersant solution AA-1. The solid content of the obtained polymer dispersant solution AA-1 was 23.2%.

[0081] (Synthesis Examples 2 and 3)

[0082] Polymer dispersant solutions AA-2 and AA-3 were obtained in the same manner as in Synthesis Example 1 except that the compositions were set as shown in Table 1. The physical properties of the obtained polymer dispersant solutions AA-2 and AA-3 are shown in Table 1. The meanings of the abbreviations in Table 1 are shown below.

[0083] MAN: Methacrylonitrile

[0084] MAA: Methacrylic acid

[0085] DMF: N,N-dimethylformamide

[0086] Table 1: Composition and physical properties of polymers obtained in Synthesis Examples 1 to 3

[0087]

[0088] (Synthesis Example 4)

[0089] Place 255.4 parts of 3-methoxy-N,N-dimethylpropionamide (MDMPA), 1.0 part of iodine, 3.7 parts of 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (trade name "V-70", manufactured by FUJIFILM Wako Chemicals Corporation) (V-70), 0.2 parts of diphenylmethane (DPM), 6.1 parts of AN10, and 26.5 parts of MAA in a reaction container. Stir while letting nitrogen flow, raise the temperature to 40°C, and polymerize for 4 hours to form an A chain. The solid content of the reaction solution is 34.8%, and the polymerization conversion calculated from the solid content is about 100%. The Mn of the formed A chain is 14800, the PDI is 1.41, and the peak molecular weight (PT) is 20700.

[0090] After adding 3.1 parts of V-70, a monomer solution containing 30.0 parts of AN, 31.8 parts of MAA and 216.9 parts of MDMPA was further added. After that, polymerization was carried out at 40°C for 4 hours to form a B chain and obtain an AB block copolymer. The solid content of the reaction solution was 29.9%, and it was confirmed that the target product was obtained basically quantitatively. The Mn of the obtained AB block copolymer was 21600, PDI was 1.52, and PT was 32700. The molecular weight of the B chain can be calculated by subtracting the Mn of the A chain from the Mn of the AB block copolymer. That is, the Mn of the B chain is 6800 and the PT is 12000.

[0091] Place 29.8 parts of NaOH (110 mol% relative to MAA) and 105.1 parts of ion exchange water in a beaker and completely dissolve NaOH to prepare a NaOH aqueous solution. Add the NaOH aqueous solution to a reaction vessel to neutralize the carboxyl group to obtain a polymer dispersant solution AB-1. The solid content of the obtained polymer dispersant solution AB-1 is 25.1%.

[0092] (Synthesis Examples 5 to 8)

[0093] Polymer dispersant solutions AB-2 to 5 were obtained in the same manner as in Synthesis Example 4 except that the compositions were set as shown in Table 2. The physical properties of the obtained polymer dispersant solutions AB-1 to 5 are shown in Table 2. The meanings of the abbreviations in Table 2 are shown below.

[0094] ·BDMPA: 3-Butoxy-N,N-dimethylpropionamide

[0095] Table 2: Composition and physical properties of polymers obtained in Synthesis Examples 4 to 8

[0096]

[0097] (Comparative Synthesis Example 1)

[0098] Put 233.3 parts of NMP in a reaction container and stir, and heat it to 70°C. In addition, put 70.0 parts of methyl methacrylate (MMA), 30.0 parts of AA, and 5.0 parts of V-65 in a beaker, dissolve V-65 completely, and prepare a monomer solution. Add the prepared monomer solution to the dropping funnel, and when the temperature in the reaction container reaches 70°C, add 1 / 3 of the total amount, and add the remaining liquid dropwise over 1.5 hours. After the addition is completed, add 1.0 part of V-65 after 2.5 hours. After maintaining at 70°C for 1 hour, raise the temperature to 80°C and maintain for 2 hours to form a polymer. After cooling, measure the solid content and confirm that all monomers are basically consumed. The Mn of the polymer is 21900 and the PDI is 2.21.

[0099] 18.3 parts of NaOH (110 mol% relative to AA) and 83.2 parts of ion exchange water were placed in a beaker to completely dissolve NaOH to prepare a NaOH aqueous solution. After the temperature in the reaction container reached 60°C or less, the NaOH aqueous solution was added to neutralize the carboxyl group to obtain a polymer dispersant solution AH-1. The solid content of the obtained polymer dispersant solution AH-1 was 23.0%.

[0100] (Comparative Synthesis Example 2)

[0101] Place 233.3 parts of NMP in a reaction container and stir, then heat to 70°C. In addition, place 85.0 parts of MMA, 15.0 parts of AA, and 5.0 parts of V-65 in a beaker, dissolve V-65 completely, and prepare a monomer solution. Add the prepared monomer solution to the dropping funnel, and when the temperature in the reaction container reaches 70°C, add 1 / 3 of the total amount, and drip the remaining liquid over 1.5 hours. After the dripping is completed, add 1.0 part of V-65 after 2.5 hours. After maintaining at 70°C for 1 hour, raise the temperature to 80°C and maintain for 2 hours to form a polymer. After cooling, measure the solid content and confirm that all monomers are basically consumed. The Mn of the polymer is 22400 and the PDI is 2.02.

[0102] 9.2 parts of NaOH (110 mol% relative to AA) and 92.4 parts of ion exchange water were placed in a beaker to completely dissolve NaOH to prepare a NaOH aqueous solution. The NaOH aqueous solution was added after the temperature in the reaction vessel reached 60°C or less. However, a polymer precipitated and an aqueous solution could not be prepared.

[0103] (Comparative Synthesis Example 3)

[0104] Put 400.0 parts of NMP in a reaction container and stir, and heat it to 70°C. In addition, put 40.0 parts of AN, 60.0 parts of AA, and 5.0 parts of V-65 in a beaker, and completely dissolve V-65 to prepare a monomer solution. Add the prepared monomer solution to the dropping funnel, and when the temperature in the reaction container reaches 70°C, add 1 / 3 of the total amount, and add the remaining liquid dropwise over 1.5 hours. After the addition is completed, add 1.0 part of V-65 after 2.5 hours. After maintaining at 70°C for 1 hour, raise the temperature to 80°C and maintain for 2 hours to form a polymer. After cooling, measure the solid content and confirm that all monomers are basically consumed. The Mn of the polymer is 19300 and the PDI is 2.42.

[0105] 46.7 parts of potassium hydroxide (KOH) (100 mol% relative to AA) and 120.0 parts of ion exchange water were placed in a beaker to completely dissolve KOH to prepare a KOH aqueous solution. After the temperature in the reaction container reached 60°C or less, the KOH aqueous solution was added to neutralize the carboxyl group to obtain a polymer dispersant solution AH-2. The solid content of the obtained polymer dispersant solution AH-2 was 15.1%.

[0106] <Preparation of Carbon Nanotube (CNT) Dispersion Liquid>

[0107] (Example 1)

[0108] In a resin container, 1.0 part of multi-walled carbon nanotubes (trade name "K-nanos100T", manufactured by KUMHO, average diameter: 11 to 13 nm, average length: 40 to 50 μm) (100T), 94.69 parts of water, 4.31 parts of polymer dispersant solution AA-1 (solid content 23.2%), and zirconia beads (diameter ) 180 parts. The CNTs were wet but settled at the bottom of the container, with a transparent layer on the top. Skandex was used for 60 minutes of dispersion treatment, and the liquid turned black uniformly, and the aggregation state of the CNTs was loosened. Next, the CNTs that were not fully dispersed by centrifugation were separated by sedimentation, and the supernatant was taken out as CNT dispersion liquid-1.

[0109] (Examples 2 to 18, Comparative Examples 1 to 4)

[0110] CNT dispersions-2 to 22 were prepared in the same manner as in Example 1 except that the formulations were as shown in Table 3. The meanings of the abbreviations in Table 3 are shown below.

[0111] MWCNT: (manufactured by Hamamatsu Carbonics Corporation, multi-walled carbon nanotube, average diameter: 10 to 40 nm, average length: 1000 μm ± 500 μm)

[0112] · SG101: (trade name "SG-101", manufactured by Zeon Corporation, single-walled carbon nanotubes, average diameter: 3 - 5 nm, average length: 100 - 600 μm)

[0113] · Tuball: (manufactured by OCSiAl, single-walled carbon nanotubes, average diameter: 1.6 ± 0.4 nm, average length: 5 μm)

[0114] Table 3: Preparation of CNT Dispersion

[0115]

[0116] <Evaluation of CNT Dispersion>

[0117] Using an E-type viscometer (measurement conditions: 25°C, rotor speed 100 rpm), measure the viscosity of the CNT dispersion at 25°C just after dispersion (initial) and after standing for 10 days. Then, calculate the change rate of viscosity after standing for 10 days based on the initial viscosity (viscosity change rate (%)), and evaluate the viscosity stability of the CNT dispersion according to the evaluation criteria shown below. Furthermore, observe the state of the CNT dispersion after standing for 10 days with an optical microscope (200 times magnification) to confirm the presence or absence of aggregates.

[0118] ◎: Viscosity change rate is less than 5%.

[0119] ○: Viscosity change rate is 5% or more and less than 10%.

[0120] ×: Viscosity change rate is 10% or more.

[0121] In addition, measure the CNT concentration of the CNT dispersion after centrifugation. A spectrophotometer is used for the measurement of CNT concentration. Specifically, measure the absorbance of a sample with a known CNT concentration to prepare a standard curve. Then, dilute the sample to a concentration at which the absorbance can be measured, measure the absorbance of the sample, and calculate the CNT concentration of the sample from the standard curve. Calculate the ratio (%) of the CNT concentration after centrifugation to the designed CNT concentration as "dispersion stability (%)". The closer the dispersion stability is to 100%, the better the dispersion of CNTs. The evaluation results of the CNT dispersion are shown in Table 4.

[0122] Table 4: Evaluation Results of CNT Dispersion

[0123]

[0124] <Preparation of Carbon Black (CB) Dispersion>

[0125] (Example 19)

[0126] In a resin container, 3.0 parts of carbon black (trade name "Li-435", manufactured by Denka Company Limited, acetylene black) (CB), 84.07 parts of water, 12.93 parts of a polymer dispersant solution AA-1 (solid content 23.2%), and 180 parts of zirconia beads (diameter ) were placed. The CB was wetted but settled at the bottom of the container, and there was a transparent layer on the upper part. Skandex was used for dispersion treatment for 60 minutes, and as a result, the liquid became uniformly black, and the aggregated state of the CB was loosened. Then, the CB that was not sufficiently dispersed after centrifugation was sedimented and separated, and the supernatant was taken out as CB dispersion-1.

[0127] (Examples 20 to 26, Comparative Examples 5 and 6)

[0128] CB dispersions - 2 to 10 were prepared in the same manner as in Example 19 described above, except that the formulations shown in Table 5 were used.

[0129] Table 5: Preparation of CB Dispersions

[0130]

[0131] <Evaluation of CB Dispersions>

[0132] Using an E-type viscometer (measurement conditions: 25 °C, rotor speed 100 rpm), the viscosities of the CB dispersions just after dispersion (initial) and after standing for 10 days were measured at 25 °C. Then, the change rate of viscosity after standing for 10 days based on the initial viscosity (viscosity change rate (%)) was calculated, and the viscosity stability of the CB dispersions was evaluated according to the evaluation criteria shown below.

[0133] ◎: The viscosity change rate is less than 5%.

[0134] ○: The viscosity change rate is 5% or more and less than 10%.

[0135] ×: The viscosity change rate is 10% or more.

[0136] Furthermore, the state of the CB dispersion after standing for 10 days was observed with an optical microscope (200 times magnification), and the presence or absence of aggregates was confirmed. The evaluation results of the CB dispersions are shown in Table 6.

[0137] Table 6: Evaluation Results of CB Dispersions

[0138]

[0139] <Preparation of CNT Dispersions Containing a Binder>

[0140] (Examples 27 to 29, Comparative Examples 7 to 8)

[0141] The CNT dispersion of the type shown in the "CNT dispersion used as raw material" in Table 7 was mixed with a binder (styrene-acrylic resin, trade name "YL-1098", manufactured by Seiko PMC Corporation) at a ratio such that the concentration of the carbon material (CNT) in the formed coating (solid content) became 3%, and then mixed using a magnetic stirrer to obtain CNT dispersions B-1 to 5 to which the binder was added.

[0142] <Evaluation of CNT dispersion containing binder>

[0143] Using an E-type viscometer (measurement conditions: 25°C, rotor speed 100rpm), the viscosity of the CNT dispersion at 25°C was measured just after dispersion (initial) and after standing for 10 days. Then, the rate of change of viscosity after standing for 10 days based on the initial viscosity (viscosity change rate (%)) was calculated, and the viscosity stability of the CNT dispersion was evaluated according to the evaluation criteria shown below. Furthermore, the state of the CNT dispersion after standing for 10 days was observed by optical microscopy (200 times), and the presence or absence of aggregates was confirmed. The results are shown in Table 7.

[0144] ◎: The viscosity change rate is less than 5%.

[0145] ○: The viscosity change rate is 5% or more and less than 10%.

[0146] ×: The viscosity change rate is 10% or more.

[0147] In addition, prepare a blank solution of the same composition as the dispersion except that it does not contain carbon material. Use the prepared blank solution to determine the baseline, and on this basis, determine the absorbance of the sample solution. Use a spectrophotometer with a quartz cuvette with an optical path length of 10 mm (trade name "Hitachi Spectrophotometer U-3310", manufactured by Hitachi High-Tech Corporation) to determine the absorbance of the sample solution. For the dilution based on the blank solution, prepare a standard curve of the absorbance at a wavelength of 580 nm that plots the change based on the dilution ratio, calculate the dilution ratio at which the aforementioned absorbance becomes 1.8±0.02, and prepare a dispersion diluted to the target concentration. In addition, it is also possible to adjust the target carbon component concentration at the stage before dispersion, or to adjust the carbon component concentration to meet the aforementioned absorbance at the initial mixing stage for dispersion. The specific method for preparing the sample solution is as follows: First, collect the dispersion in a plastic bottle (polyethylene bottle), and add an appropriate amount of blank solution based on the dilution ratio calculated according to the standard curve. The mixture was stirred for 30 seconds using a vortex mixer (manufactured by Scientific Industries, Inc.) to obtain the absorbance A at a wavelength of 580 nm. 580The absorbance A of the sample solution obtained at a wavelength of 380 nm was measured. 380 and the absorbance A at a wavelength of 780 nm 780 , and calculate the absorbance ratio (A 380 / A 780 ).

[0148] <Evaluation of coating film>

[0149] The CNT dispersion was applied to a 100 μm thick PET film (trade name "Lumirror", manufactured by Toray Industries, Inc.) using a bar coater, and then dried in an electric oven at 90°C for 30 minutes to remove volatile components to form a coating film with a thickness of 1 μm. The surface resistivity of the formed coating film is shown in Table 7. The surface resistivity exceeds 10 5 In the case of Ω / sq, a high resistance resistivity meter (trade name "Hiresta-UP MCP-HT450", manufactured by Nittoseiko Analytech Co., Ltd.) was used to calculate the average surface resistivity of the coating film measured at 5 points under 10 V. In addition, the surface resistivity is 10 5 When the surface resistivity was Ω / sq or less, the average value of the surface resistivity of the coating film measured at 5 points under application of 10 V was calculated using a low-resistance resistivity meter (trade name "Loresta-GPMCP-T610", manufactured by Nittoseiko Analytech Co., Ltd.).

[0150] Table 7: Evaluation results of cNT dispersion (binder added)

[0151]

[0152] <Application Examples>

[0153] (Application example 1: Battery materials (negative electrode))

[0154] The following materials are used to manufacture the negative electrode of a lithium-ion battery.

[0155] [Negative electrode active agent]

[0156] Graphene (manufactured by FUJIFILM Wako Chemicals Corporation)

[0157] Silicon monoxide (manufactured by FUJIFILM Wako Chemicals Corporation)

[0158] [Binder]

[0159] 10% polyacrylic acid aqueous solution (trade name "CLPA-C07", manufactured by FUJIFILM Wako Chemicals Corporation)

[0160] Carboxymethyl cellulose (trade name "CMC DAICEL 2200", manufactured by DAICEL MIRAIZU LTD.)

[0161] Styrene-butadiene copolymer latex (trade name: "NALSTER SR-112", manufactured by NIPPON A&L INC.)

[0162] Using a planetary mixer, 15 parts of silicon monoxide, 85 parts of graphene, 3 parts of the dispersion prepared in Example 4, 30 parts of a 10% polyacrylic acid aqueous solution, 21.6 parts of carboxymethyl cellulose and 0.4 parts of styrene-butadiene copolymer latex were mixed to obtain a negative electrode material. It should be noted that other mixing devices such as a rotation / revolution mixer can also be used for mixing. The mass per unit area after drying is 15 mg / cm 2 The negative electrode material was applied on a copper foil with a thickness of 20 μm using an applicator. After being placed in an oven set at 120°C for 30 minutes to dry, it was rolled using a roller press to obtain a negative electrode. The volume resistivity of the obtained negative electrode was 0.18 Ω·cm.

[0163] (Application example 2: Battery materials (negative electrode))

[0164] A negative electrode was produced in the same manner as in Application Example 1, except that the dispersion produced in Example 13 was used. The volume resistivity of the produced negative electrode was 0.16 Ω·cm.

[0165] (Application example 3: Battery materials (negative electrode))

[0166] A negative electrode was produced in the same manner as in Application Example 1 except that the dispersion produced in Comparative Example 2 was used. The volume resistivity of the produced negative electrode was 0.49 Ω·cm. As described above, it can be seen that a negative electrode having a smaller volume resistivity can be produced by using a dispersion having a good dispersibility evaluation.

[0167] (Application example 4: Battery materials (negative electrode))

[0168] Using a planetary mixer, 15 parts of silicon monoxide, 85 parts of graphene, 3 parts of the dispersion prepared in Example 13, and 32 parts of a 10% polyacrylic acid aqueous solution were mixed to obtain a negative electrode material. The mass per unit area after drying was 15 mg / cm 2The negative electrode material was applied on a copper foil with a thickness of 20 μm using an applicator. After being placed in an oven set at 120°C for 30 minutes to dry, it was rolled using a roller press to obtain a negative electrode. The volume resistivity of the obtained negative electrode was 0.15Ω·cm. From the above, it can be seen that by unifying the binder and the dispersant with a (meth) acrylic resin, a negative electrode with a smaller volume resistivity value can be manufactured.

[0169] Industrial Applicability

[0170] The carbon material dispersion of the present invention is useful as a constituent material of water-based paints, water-based inks, plastic molded products, etc. that exhibit properties such as high electrical conductivity and high thermal conductivity, and is suitable for various uses such as battery materials, electronic component trays, IC chip covers, electromagnetic wave shielding bodies, automotive components, and robot components.

Claims

1. A carbon material dispersion comprising: at least one carbon material selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite and graphene, water, and a polymer dispersant, The polymer dispersant is a polymer having at least a portion of carboxyl groups neutralized by a base and composed of 50 to 80% by mass of a structural unit (1) derived from (meth)acrylonitrile and 20 to 50% by mass of a structural unit (2) derived from (meth)acrylic acid, wherein: The total of the structural unit (1) and the structural unit (2) is 100% by mass. The number average molecular weight of the polymer is 10,000 to 50,000. The polymer is an AB block copolymer comprising a polymer segment A and a polymer segment B, The polymer segment A is composed of 70 to 90% by mass of a structural unit (1-A) derived from acrylonitrile and 10 to 30% by mass of a structural unit (2-A) derived from methacrylic acid, wherein the total of the structural unit (1-A) and the structural unit (2-A) is 100% by mass. The polymer segment B is composed of 10 to 70% by mass of a structural unit (1-B) derived from acrylonitrile and 30 to 90% by mass of a structural unit (2-B) derived from methacrylic acid, wherein the total of the structural unit (1-B) and the structural unit (2-B) is 100% by mass. The number average molecular weight of the polymer segment A is 8000 to 40000, and the molecular weight distribution is less than 1.

8. The content of carboxyl groups in the polymer segment A is less than the content of carboxyl groups in the polymer segment B.

2. The carbon material dispersion according to claim 1, wherein The base is at least one selected from the group consisting of lithium hydroxide, sodium hydroxide and potassium hydroxide, The amount of the base is an amount corresponding to 50 to 120 mol % of the carboxyl group.

3. The carbon material dispersion according to claim 1 or 2 further contains at least one water-soluble organic solvent selected from the group consisting of dimethylformamide, dimethylacetamide, diethylacetamide, N-methylpyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, tetramethylurea, 1,3-dimethylimidazolidinone and acetonitrile.

4. The carbon material dispersion according to any one of claims 1 to 3, wherein The content of the polymer dispersant is 10 to 350 parts by mass relative to 100 parts by mass of the carbon material. The content of the carbon material is 15 mass % or less. 5 . The carbon material dispersion according to claim 1 , further comprising a binder resin.

6. Use of the carbon material dispersion according to any one of claims 1 to 5 for producing any product selected from the group consisting of paint, ink, coating agent, resin molding material, conductive material, thermal conductive material and antistatic material.

7. Use of the carbon material dispersion according to any one of claims 1 to 5 for producing a product including a battery material and a mechanical part having a coating film formed of the carbon material dispersion.

Citation Information

Patent Citations

  • Ink containing carbon nanotube

    JP2010174084A

  • Conductive coating composition and method for producing conductive film using the same

    JP2013537570A